THE EFFECTIVENESS OF USING BLENDED LEARNING STRATEGY IN THE ACADEMIC ACHIEVEMENT BY SEVENTH-GRADE BASIC STUDENTS IN THE SUBJECT OF KURDISH LANGUAGE - Saeed, Diyar (Humanities Journal of University of Zakho, 2024)
The current study aims to identify the effectiveness of using the blended learning strategy in the academic achievement of seventh-grade students in the Kurdish language subject. The research sample consisted of (114) male and female students from the seventh grade in basic education schools for boys and girls in the city of Zakho for the academic year (2022-2023). It was chosen intentionally by stratified random method from the research community according to the gender variable, then the researcher divided the sample into four equal groups in several variables based on the factorial experimental design (2X2) in the variables of teaching method and gender. The two experimental groups studied the Kurdish language subject according to the blended learning strategy, while the two control groups studied the same subject traditionally. The researcher verified the validity of the content of the test and extracted its psychometric characteristics as well as its stability. After collecting data from the research sample and processing it statistically using the two-way factor analysis of variance test according to the variables of gender, teaching method, and the interaction between them, the results indicated: 1- There is a statistically significant difference at the level (0.05) between the averages of the Kurdish language achievement among the members of the research groups according to the gender variable in favor of females and the method in favor of the blended learning strategy. 2- There is no statistically significant difference at the level (0.05) between the averages of the members of the research groups in the achievement of the Kurdish language according to the interaction of the variables of gender and method. In light of the results, the researcher came out with several conclusions, including the possibility of applying the blended learning strategy in teaching the Kurdish language to students in basic education. The researcher also put forward some recommendations and proposals in the form of titles for future research.